Quantification of microvessels in canine lymph nodes - Tonar, Zbynĕk; Egger, Gunter F; Witter, Kirsti; Wolfesberger, Birgitt (Microscopy research and technique, 2008)
Quantification of microvessels in tumors is mostly based on counts of vessel profiles in tumor hot spots. Drawbacks of this method include low reproducibility and large interobserver variance, mainly as a result of individual differences in sampling of image fields for analysis. Our aim was to test an unbiased method for quantifying microvessels in healthy and tumorous lymph nodes of dogs. The endothelium of blood vessels was detected in paraffin sections by a combination of immunohistochemistry (von Willebrand factor) and lectin histochemistry (wheat germ agglutinin) in comparison with detection of basal laminae by laminin immunohistochemistry or silver impregnation. Systematic uniform random sampling of 50 image fields was performed during photo-documentation. An unbiased counting frame (area 113,600 microm(2)) was applied to each micrograph. The total area sampled from each node was 5.68 mm(2). Vessel profiles were counted according to stereological counting rules. Inter- and intraobserver variabilities were tested. The application of systematic uniform random sampling was compared with the counting of vessel profiles in hot spots. The unbiased estimate of the number of vessel profiles per unit area ranged from 100.5 +/- 44.0/mm(2) to 442.6 +/- 102.5/mm(2) in contrast to 264 +/- 72.2/mm(2) to 771.0 +/- 108.2/mm(2) in hot spots. The advantage of using systematic uniform random sampling is its reproducibility, with reasonable interobserver and low intraobserver variance. This method also allows for the possibility of using archival material, because staining quality is not limiting as it is for image analysis, and artifacts can easily be excluded. However, this method is comparatively time-consuming.
Keywords: psi; reprodukovatelnost výsledků; Immunohistochemistry; patologie; Reproducibility of Results; cévy; Dogs; cévní endotel; imunohistochemie; Staining and Labeling; barvení a značení; Blood Vessels; Pathology; nádory; Endothelium, Vascular; Animals; Lymph Nodes; zvířata; biometrie; Neoplasms; Biometry; lymfatické uzliny